Odpowiedź :
Odpowiedź:
( 3 i 4/5 :2,5) + (6- 3/5)= (19/5 : 25/10) + ( 5 i 5/5 - 3/5)=
= ( 19/5 *10/25) + 5 i 2/5 ( skracamy 5 i 10 przez 5)= 19*2/25+ 5 i 10/25=
= 38/25 + 5 i 10/25= 1 i 13/25+ 5 i 10/25= 6 i 23/25
Szczegółowe wyjaśnienie:
Obliczenia
[tex](3\frac{4}{5}:2,5)+(6-\frac{3}{5})=(\frac{19}{5}:2\frac{5}{10})+(5\frac{5}{5}-\frac{3}{5})=\\\\=\frac{19}{5}:2\frac{1}{2}+5\frac{2}{5}=\frac{19}{5}:\frac{5}{2}+5\frac{2}{5}=\frac{19}{5}\cdot\frac{2}{5}+5\frac{2}{5}=\frac{38}{25}+5\frac{2}{5}=\\\\=1\frac{13}{25}+5\frac{2}{5}=1\frac{52}{100}+5\frac{4}{10}=1,52+5,4=\boxed{6,92}[/tex]